The spooky tail of Prewitt peacock - Peet, Bill. (Boston : Houghton Mifflin, 1973)
When Prewitt's shamefully scraggly tail develops the appearance of a scary greeneyed monster, the other peacocks decide it has to go.
"Sandpiper Houghton Mifflin books"--Back cover.
Keywords: Peafowl -- Fiction